Layaran Pintas Sdn Bhd / Nur Liyana Shaharullah - Shaharullah, Nur Liyana (Faculty of Business and Management, 2023)
To date, having a higher degree or any qualification doesn’t automatically guarantee an employment or becomes an indicator towards job competencies. Instead, graduates should have knowledge of relevant and current practical experience, soft skills as well as positive attitudes to enable them to compete in a job market. Therefore, the industrial training program provides opportunity for the students to explore what they have learnt in the class then apply them in the real working world, hence preparing them for their career soon. This training will give experience required by graduates to increase the level of employability. Students in the Business Management program must complete Internship (MGT666) as a final-semester requirement. The main purpose of the internship is to learn via on-the-job training in practical environment and to apply the knowledge acquired during the studies in a real-world scenario. I was placed as intern in the marketing and sales department at Layaran Pintas Sdn. Bhd. for six months, from 1st March 2023 until 15th August 2023, for the purpose of compiling this internship report. There I was able to gain a practical experiences and skills like a normal employee thru various given assignments. In this report, you will discover this company’s SWOT which I run through with my manager. The SWOT exercise really challenged my analytical and critical thinking in resolving issues. Even though challenging, I find it very interesting. I put a lot of man hours interviewing staffs, searching for relevant articles and team discussions for this exercise. I really hope I can come across with the same exercise in my future job.